2001
DOI: 10.1207/s15324796abm2301_10
|View full text |Cite
|
Sign up to set email alerts
|

Religious attendance increases survival by improving and maintaining good health behaviors, mental health, and social relationships

Abstract: Several recent prospective analyses involving community-based populations have demonstrated a protective effect on survival for frequent attendance at religious services. How such involvement increases survival are unclear. To test the hypothesis that religious attendance might serve to improve and maintain good health behaviors, mental health, and social relationships, changes and consistencies in these variables were studied between 1965 and 1994 for 2,676 Alameda County Study participants, from 17 to 65 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
283
6
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 487 publications
(314 citation statements)
references
References 31 publications
22
283
6
3
Order By: Relevance
“…There is a large literature suggesting that attending religious services is associated with better health (102)(103)(104). Although much of the literature is methodologically weak, there are now numerous well-designed longitudinal studies that suggest that regular religious service attendance is associated with greater longevity (105-110), a 30% lower incidence of depression (38,107,111), a fivefold lower rate of suicide (112), better survival from cancer, and numerous other outcomes (102,104). Importantly, the evidence suggests that it is attending religious services, rather than private practices or self-assessed spirituality or religiosity, that is most strongly predictive of health (106,113).…”
Section: Prominent Pathways To Human Flourishingmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a large literature suggesting that attending religious services is associated with better health (102)(103)(104). Although much of the literature is methodologically weak, there are now numerous well-designed longitudinal studies that suggest that regular religious service attendance is associated with greater longevity (105-110), a 30% lower incidence of depression (38,107,111), a fivefold lower rate of suicide (112), better survival from cancer, and numerous other outcomes (102,104). Importantly, the evidence suggests that it is attending religious services, rather than private practices or self-assessed spirituality or religiosity, that is most strongly predictive of health (106,113).…”
Section: Prominent Pathways To Human Flourishingmentioning
confidence: 99%
“…There is also some experimental evidence that encouragement to prayer increases forgiveness, gratitude, and trust (118)(119)(120). Finally, concerning close relationships, there is evidence from longitudinal studies that attending religious services decreases the likelihood of divorce (107,121,122), increases the likelihood of subsequently making new friends, and of marrying, and increases social support (107,114,123). The effect of religious community, and specifically religious service attendance, on these various aspects of flourishing, is thus substantial.…”
Section: Prominent Pathways To Human Flourishingmentioning
confidence: 99%
“…However, these associations present an interesting puzzle, because an overarching explanatory mechanism that might explain them has not been identified. Historically, theorists have focused on explanations such as (a) religion's ability to prescribe healthpromoting behaviors and proscribe health-compromising ones (T. D. Hill, Burdette, Ellison, & Musick, 2006;Strawbridge, Shema, Cohen, & Kaplan, 2001); (b) religion's ability to confer social support (Joiner, Perez, & Walker, 2002); (c) religion's ability to socialize children to conform with society's norms (Baier & Wright, 2001); and (d) religion's ability to promote effective coping with stress (Ano & Vasconcelles, 2005;Pargament, 1997).To be sure, all of these explanations are important, but the list is incomplete. George, surmised that only 35% to 50% of the relationship between religiousness and various measures of health and well-being could be explained on the basis of the explanatory variables such as social support, health behaviors, and coping.…”
mentioning
confidence: 99%
“…There were similar findings regarding the relationships between religion, religiosity, spirituality, and/or religious commitment and nutrition, and various predictors for nutritional intake (Merrill & Thygerson, 2001;Pearson, Turner, Young, & Knickerbocker, 2007;Strawbridge, Shema, Cohen, & Kaplan, 2001). In a literature review conducted by Koenig (2012), he found that religious individuals tend to consume healthy diets.…”
Section: Religious Commitment and Dfimentioning
confidence: 76%